2017
DOI: 10.1088/1752-7163/aa5359
|View full text |Cite
|
Sign up to set email alerts
|

A collection system for dry solid residues from exhaled breath for analysis via atomic force microscopy

Abstract: Exhaled air contains sub-micron droplets of lung liquid, which potentially bear biomarkers of lung diseases. After dehydration they form dry residue particles (DRPs). As a first step in developing techniques to characterize individual DRPs, a new electrostatic collector was designed in which DRPs are charged within a unipolar corona charger, concentrated in a cone funnel, and deposited onto a limited area of a highly oriented pyrolytic graphite surface. The collector captures 80%-90% of DRPs at an optimal flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Particularly, through mass spectra of particles, the literature has revealed the presence of nonvolatile solutes such as potassium, calcium, and chorine contents in the faceted particles ( Papineni et al, 1997 , and Morozov & Mikheev, 2017 ), which are likely to be generated from the alveolar fluid from the lower respiratory tract ( Johnson & Morawska, 2009 ). In addition, Morozov and Mikheev (2017) suggested that these faceted particles can contain lipids and hydrophobic proteins which are soluble in organic solvents. Noteworthily, such faceted particles could be the residues of droplet evaporation and may correspond to the long-lasting dry particles reported in the experiments of Stadnytskyi et al (2020) .…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, through mass spectra of particles, the literature has revealed the presence of nonvolatile solutes such as potassium, calcium, and chorine contents in the faceted particles ( Papineni et al, 1997 , and Morozov & Mikheev, 2017 ), which are likely to be generated from the alveolar fluid from the lower respiratory tract ( Johnson & Morawska, 2009 ). In addition, Morozov and Mikheev (2017) suggested that these faceted particles can contain lipids and hydrophobic proteins which are soluble in organic solvents. Noteworthily, such faceted particles could be the residues of droplet evaporation and may correspond to the long-lasting dry particles reported in the experiments of Stadnytskyi et al (2020) .…”
Section: Resultsmentioning
confidence: 99%
“…It consisted of a thermostated metal base to which a plastic dumbbellshaped cap is attached with screws. The air is pumped from the cap at a rate of 2.2 l min −1 , while exhaled air is fed in through a tube with an inner diameter of 0.7 mm and accelerates to ∼100 m s −1 , so that 50% of MLFs with a size of 470 nm are captured [23].…”
Section: Impactorsmentioning
confidence: 99%
“…A few reports have described the analytical application of such electro-precipitation procedures to sample airborne particles, which are then imaged under an electron microscope [39] or used to monitor environmental bioaerosols [40,41]. To the best of our knowledge, our recent paper was the first report describing the use of an electrostatic collector to analyse dry residues of MLFs with AFM [23]. The collector allows dry residues to settle on graphite and other conducting substrates with high efficiency because it uses a special electrostatic 'funnel' made of a polymer mesh that directs the charged particles onto a conducting substrate to produce a highly dense deposition suitable for AFM imaging.…”
Section: Electrostatic Collectormentioning
confidence: 99%
See 2 more Smart Citations